Streptococcus intermedius - : An Uncommon Cause of Severe Pulmonary Infections in Immunocompetent Patients (Translation: The University of Toledo Journal of Medical Sciences, 2023)
Please view the PDF to see the formatted meeting abstract.
Keywords: Pulmonology; Case Reports